1999
DOI: 10.1017/s0033291799008429
|View full text |Cite
|
Sign up to set email alerts
|

Fears and phobias: reliability and heritability

Abstract: Lifetime histories of unreasonable fears and phobias assessed at personal interview have substantial unreliability. Correcting for unreliability, the liability to fears and their associated phobias is moderately heritable. Individual-specific environmental experiences play an important role in the development of phobias, while familial-environmental factors appear to be of little aetiological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(137 citation statements)
references
References 53 publications
11
122
3
1
Order By: Relevance
“…The only large twin sample that has comprehensively examined the genetics of phobias in adults is the Virginia Twin Registry. Analyses from that sample have found that genetics is largely responsible for twin resemblance in females (10) and males (11), with reliability-corrected estimates of heritability that ranged from 0.46 for situational phobia to 0.67 for agoraphobia (12). Two other broad findings emerged from these analyses.…”
Section: Introductionmentioning
confidence: 91%
“…The only large twin sample that has comprehensively examined the genetics of phobias in adults is the Virginia Twin Registry. Analyses from that sample have found that genetics is largely responsible for twin resemblance in females (10) and males (11), with reliability-corrected estimates of heritability that ranged from 0.46 for situational phobia to 0.67 for agoraphobia (12). Two other broad findings emerged from these analyses.…”
Section: Introductionmentioning
confidence: 91%
“…More recently, Kendler and colleagues provided a higher heritability estimate of SAD (= .51), correcting for unreliability by means of conducting repeated assessments 8 years apart (Kendler, Karkowski, & Prescott, 1999). A recent meta-analysis of twin studies reported a heritability estimate of .65 (Beatty, Heisel, Hall, Levine, & La France, 2002).…”
Section: Twin and Family Studiesmentioning
confidence: 99%
“…Indeed, focusing upon a single measure of phobias may have limitations, as suggested by research demonstrating that information about fear and phobias assessed at personal interviews shows substantial unreliability (15).…”
Section: Finding Gene-environment Interactions For Phobiasmentioning
confidence: 99%